Carbonate substitution significantly affects the structure and mechanics of carbonated apatites. (1st March 2021) - Wingender, Brian; Azuma, Masashi; Krywka, Christina; Zaslansky, Paul; Boyle, John; Deymier, Alix
Abstract: Bone mineral comprises nanoparticles of carbonate-substituted bioapatite similar to hydroxylapatite. Yet mechanical values of macroscopic-sized geological hydroxylapatite are often used to model bone properties due to a lack of experimental data for bioapatite. Here, we investigated the effects of carbonate substitution and hydration on biomimetic apatite response to load using in situ hydrostatic pressure loading and synchrotron x-ray diffraction. We find that increasing carbonate levels reduced the bulk modulus and elastic strain ratio. Elastic constants, determined using computational optimization techniques, revealed that compliance values and elastic moduli decreased with increasing carbonate content, likely a result of decreased bond strength due to CO3 2− substitution and Ca 2+ loss. Hydration environment had no clear effects on the elastic properties likely due to dissolution and reprecipitation processes modifying the crystal structure organization. These results reinforce the need to consider carbonate composition when selecting mechanical properties and provide robust data for carbonate-substituted apatite stiffness. Graphical abstract: Image, graphical abstract